Serious Hypokalemia Associated with Abiraterone Acetate in Patients with Castration-Resistant Prostate Cancer - Yutaka Yamamoto; Yasunori Akashi; Takahumi Minami; Masahiro Nozawa; Keisuke Kiba; Motokiyo Yoshikawa; Akihide Hirayama; Hirotsugu Uemura (Case Reports in Urology)
Introduction. The treatment strategy for castration-resistant prostate cancer (CRPC) has changed with the approval of several new agents. In 2011, abiraterone acetate was approved for the treatment of metastatic CRPC; however abiraterone is known to cause mineralocorticoid excess syndrome characterized by hypokalemia, fluid retention, and hypertension. We experienced two cases of grade 4 hypokalemia associated with abiraterone treatment. Case Presentation. Case 1: a 71-year-old male with metastatic CRPC presented with convulsive seizures two weeks after receiving abiraterone plus prednisone. The serum potassium level was 2.1mEq/l. We determined that convulsive seizure was caused by hypokalemia associated with abiraterone. Case 2: a 68-year-old male with metastatic CRPC presented with severe lethargy one month after receiving abiraterone plus prednisone. The serum potassium level was 1.7mEq/l and we concluded that severe lethargy was caused by hypokalemia associated with abiraterone. They were treated with potassium supplementation and increased prednisone following withdrawal of abiraterone. Discussion. The two patients had been on glucocorticoid therapy before abiraterone therapy. Prolonged administration of exogenous glucocorticoid can lead adrenocortical insufficiency and consequently reduce endogenous glucocorticoid production. This situation may increase the risk of abiraterone-induced mineralocorticoid excess. To reduce the risk of abiraterone-induced hypokalemia, evaluation of adrenocortical insufficiency is required.